Knowledge Concealment in the Malaysian Public Administration: The Roles of Rewards, Internal Competition, and Interpersonal Distrust - Suhaila Osman; Norhayati Hussin; Mohd Sazili Shahibi; Ahmad Nadzri Mohamad (European Conference on Knowledge Management, 2026)
Knowledge sharing is essential for an efficient and innovative public sector, yet it is often hindered by knowledge concealment. This study examines knowledge concealment as an outcome of the lack of rewards for knowledge sharing and internal competition, with interpersonal distrust as the mediating mechanism, within the framework of the Social Exchange Theory (SET). Data were collected from 276 Malaysian Administrative and Diplomatic Officers (ADOs) and analysed using SPSS and Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that both the lack of rewards for sharing knowledge and internal competition significantly increase knowledge concealment. Mediation analysis shows that interpersonal distrust significantly mediates the relationship between lack of rewards and knowledge concealment, indicating that perceived inequity in reward systems weakens trust, which subsequently increases knowledge concealment. However, interpersonal distrust does not mediate the relationship between internal competition and knowledge concealment. This suggests that in highly structured public sector environments, internal competition operates as a direct structural driver of knowledge concealment rather than through relational trust mechanisms. This study extends the SET by proving that exchange-based mechanisms operate differently in bureaucratic contexts. Specifically, lack of rewards triggers relational distrust that leads to knowledge concealment, while internal competition directly influences knowledge concealment. This suggests that the applicability of the SET may vary in highly bureaucratic contexts, where institutional rules, hierarchical structures, and formalised career systems shape employee behaviour beyond relational exchange processes. Practically, the findings highlight the importance of strengthening reward systems and trust-building mechanisms in public sector organisations. Transparent recognition, fair performance appraisal, and collaborative incentives are essential to encourage knowledge sharing and reduce knowledge concealment. By improving both structural incentives and relational trust, public organisations can support more effective knowledge sharing practices.